Drivers of social equity in renewable energy at the municipal level: the case of local Japanese energy policy and preferences. Issue 3 (3rd May 2020) - Fraser, Timothy; Chapman, Andrew J.
ABSTRACT: Recent research has allowed us to quantify the costs and benefits of adopting renewable energy in specific municipalities, but how do these outcomes vary among communities at the national scale? This study uses survey responses from 47 Japanese municipalities to model these impacts and identifies key technological, social, and demographic factors that shape which communities benefit more from the renewable energy transition. On average, introducing renewable energy improves social equity, any financial burden on electricity prices is born most by wealthier residents, not the poor, and towns are predisposed to benefit from renewables no matter the amount introduced. To improve these impacts, towns can increase the amount of solar they host, or they can adjust the amount of CO2 emissions, PM emissions, tax revenue, jobs gained, or unpopular renewable power plants in their town. However, preferences and demographics matter as well. Age, education, and local preferences in favor of employment and community development all significantly relate to equity potential outcomes. Policymakers should consider adjusting their local energy priorities using these levers if they hope to engineer a renewable energy transition that is both positive and popular for their constituents.